2016
DOI: 10.1158/2159-8290.cd-15-1347
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ1-Mediated SMAD3 Enhances PD-1 Expression on Antigen-Specific T Cells in Cancer

Abstract: Programmed Death-1 (PD-1) is a co-inhibitory receptor that down-regulates the activity of tumor-infiltrating lymphocytes (TIL) in cancer and of virus-specific T cells in chronic infection. The molecular mechanisms driving high PD-1 expression on TIL have not been fully investigated. We demonstrate that transforming growth factor-β1 (TGF-β1) directly enhances antigen-induced PD-1 expression through Smad3-dependent, Smad2-independent transcriptional activation in T cells in vitro and in TIL in vivo. The PD-1hi s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
158
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 214 publications
(177 citation statements)
references
References 69 publications
(82 reference statements)
10
158
0
Order By: Relevance
“…Consistent with a recent report (Park et al, 2016), we confirmed that translocated Smad proteins occupy crucial regulatory regions upstream of the Pdcd1 transcriptional start site in response to Tgf-β. Interestingly, we found that the segment of CR-C occupied by Satb1 overlaps with, or is adjacent to, the Smad protein binding site.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with a recent report (Park et al, 2016), we confirmed that translocated Smad proteins occupy crucial regulatory regions upstream of the Pdcd1 transcriptional start site in response to Tgf-β. Interestingly, we found that the segment of CR-C occupied by Satb1 overlaps with, or is adjacent to, the Smad protein binding site.…”
Section: Discussionsupporting
confidence: 92%
“…A recent report identified that Tgf-β-driven PD-1 expression is associated with binding of Smad3 to PD-1 promoter regions (Park et al, 2016). Our ChIP-PCR experiments confirmed that, in response to Tgf-β, Smad2/3 bind to CR-C , one of the conserved upstream regulatory regions hypersensitive to DNase I that control PD-1 expression in response to CD8 T cell activation (Lu et al, 2014; Oestreich et al, 2008) (Figure 3F).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that cancer‐derived TGF‐β play a critical role in immune suppression occurring in cancer patients. Similarly, it was reported that TGF‐β upregulated PD‐1 expression on T cells in cancer patients . In addition, PD‐1 induction through TCR activation was partially regulated by endogenous TGF‐β .…”
Section: Introductionmentioning
confidence: 61%
“…Blocking TGF‐β enhanced the CD8 + T cell‐mediated antitumor ability . TGF‐β was identified as an immune suppressor that increased PD‐1 expression on antigen‐specific CD8 + T cells in cancer . Furthermore, the major source of TGF‐β in tumor tissues was verified to be secreted by MDSCs in ESCC.…”
Section: Discussionmentioning
confidence: 97%
“…Rosa26 reporter mice (R26 EGFP ) were previously described (57) and were purchased from the Jackson Laboratory (catalog 012429). LoxP-targeted Smad2/3 mice were recently described as well (58). PCR genotyping used the primers Smad3 forward 5′-GTTTACTGGACTGAGGTTGGCTGTGGC-3′ and reverse 5′-GTACAGATTGGCCACTCCGGTCACTG-3′, which generated a 390-bp product recognizing loxP-targeted exons 2/3 and 287-bp WT fragments.…”
Section: Methodsmentioning
confidence: 99%